Strategies and new developments to control pertussis, an actual health problem - Gaillard, María Emilia (2015)
The aim of this article is to describe the current epidemiological situation of pertussis, as well as different short-term strategies that have been implemented to alleviate this threat. The state of the art of the development of new vaccines that are expected to provide long-lasting immunity against pertussis was also included.